S30 Nutrition and Exercise Rehabilitation in Obesity Hypoventilation Syndrome (NERO): A Pilot Randomised Controlled Trial. (12th November 2015) - Mandal, S; Suh, ES; Harding, R; Vaughan-France, A; Ramsay, M; Connolly, B; Bear, D; McLaughlin, H; Greenwood, S; Polkey, M; Elliott, M; Douiri, A; et al.
Abstract : Introduction: We have previously shown that treatment of obesity hypoventilation syndrome (OHS) with non-invasive ventilation (NIV) results in weight reduction and an increase in physical activity (Murphy et al ., 2012). We therefore hypothesised that a multi-modal rehabilitation programme, in addition to NIV, would lead to enhanced weight loss. Method: We conducted a randomised controlled trial of NIV alone vs. NIV and a personalised rehabilitation programme in patients with OHS. Subjects in the intervention group received a bespoke diet and exercise regime, from a dietician and physiotherapist. All patients, in both groups, were reviewed monthly for 3 months. Anthropometrics, exercise capacity and health related quality of life (HQRL) were measured at baseline and at 3 months. The primary outcome measure at 3 months was weight loss. Secondary outcomes included: body mass index (BMI), neck circumference (NC), waist circumference (WC), hip circumference (HC) blood pressure (BP), rectus femoris cross-sectional area (RFCSA ) and quadriceps maximal voluntary contraction (QMVC), 6 min walk distance (6MWD) and HRQL measures. Results: 37 subjects were randomised with data from 30 patients analysed at 3 months (15 in each group). There were no differences between the groups in all parameters measured at baseline. The intervention group showed greater weight loss than the control group (-11.9 ± 6.7 vs. - 2.4 ± 6.2 kg; p < 0.0001). There were also differences in NC, WC and HC (all p < 0.001, Table 1 ) with an improvement in BP observed in the intervention group (Table 1 ). In addition, there was an increase in weight corrected RFCSA and muscle strength (p < 0.0001, Table 1 ) with an increase in 6MWD in the intervention group (122 ± 161 vs. 46 ± 60 m; p = 0.005; Table 1 ). Finally, HRQL improved in the intervention group as evidenced by a greater reduction in Epworth sleepiness score, an increase in severe respiratory insufficiency questionnaire sum score and a greater decrease in the hospital and anxiety depression score (Table 1, all p < 0.0001). Conclusion: In patients with OHS, the addition of a hospital-home hybrid personalised diet and exercise programme to standard NIV was shown to enhance weight loss as well as, skeletal muscle area and strength, exercise capacity and HRQL. Reference: 1 Murphy PB, Davidson C, Hind MD, et al. Volume targeted versus pressure support non-invasive ventilation in patients with super obesity and chronic respiratory failure: a randomised controlled trial. Thorax . 2012;67 :727–34